Electrochemically induced in vitro focal hypoxia in human neurons - Wong, Joseph J. Y.; Varga, Balazs V.; Káradóttir, Ragnhildur Thóra; Hall, Elizabeth A. H. (Frontiers in Cell and Developmental Biology, 2022)
Focalised hypoxia is widely prevalent in diseases such as stroke, cardiac arrest, and dementia. While in some cases hypoxia improves cellular functions, it mostly induces or exacerbates pathological changes. The lack of methodologies that can simulate focal acute hypoxia, in either animal or cell culture, impedes our understanding of the cellular consequences of hypoxia. To address this gap, an electrochemical localised oxygen scavenging system (eLOS), is reported, providing an innovative platform for spatiotemporal in vitro hypoxia modulation. The electrochemical system is modelled showing O2 flux patterns and localised O2 scavenging and hypoxia regions, as a function of distance from the electrode and surrounding flux barriers, allowing an effective focal hypoxia tool to be designed for in vitro cell culture study. O2 concentration is reduced in an electrochemically defined targeted area from normoxia to hypoxia in about 6 minutes depending on the O2-flux boundaries. As a result, a cell culture-well was designed, where localised O2 scavenging could be induced. The impact of localised hypoxia was demonstrated on human neural progenitor cells (hNPCs) and it was shown that miniature focal hypoxic insults can be induced, that evoke time-dependent HIF-1α transcription factor accumulation. This transcription is “patterned” across the culture according to the electrochemically induced spatiotemporal hypoxia gradient. A basic lacunar infarct model was also developed through the application of eLOS in a purpose designed microfluidic device. Miniature focal hypoxic insults were induced in cellular processes of fully oxygenated cell bodies, such as the axons of human cortical neurons. The results demonstrate experimentally that localised axonal hypoxic stress can lead to significant increase of neuronal death, despite the neurons remaining at normoxia. This suggests that focal hypoxic insult to axons alone is sufficient to impact surrounding neurons and may provide an in vitro model to study the impact of microinfarcts occurring in the deep cerebral white matter, as well as providing a promising tool for wider understanding of acute hypoxic insults with potential to uncover its pathophysiology in multiple diseases.